Preferensi Masyarakat Terhadap BRT Trans Semarang Koridor I - Bagas Atmawan; Widjonarko Widjonarko (Jurusan Perencanaan Wilayah dan Kota, 2018)
Semarang City Government in 2009 inaugurated the public transportation called Bus Rapid Transit (BRT) Trans Semarang. BRT Trans Semarang has 6 corridors in total and one of them named Corridor I. BRT Trans Semarang Corridor 1 is not the only way to solve the transportation problems in Semarang directly. It has been operating for about 8 years, but the load factor from Trans Semarang Corridor I is still below the standard set by the government and an increase in the number of private vehicles. These are indicating that BRT Trans Semarang Corridor I not become the main mode of transportation of the community in performing daily activities. Based on the problems, this study aims to determine the determinant factors that affect the public preference to BRT Trans Semarang Corridor I. The method of this study is a quantitative method. While the analysis is factor analysis which is used to identify the relationship structure among variables by looking at the correlation between them. In addition, the study also used descriptive statistical analysis as a complement and supporting data only. The study shows that people's preference around Trans Semarang Corridor I is still low, as many as 39.4% of people prefer Trans Semarang Corridor I as the main mode of transportation in performing its daily activities. While the people who still have not used Trans Semarang Corridor I is about 60.6% of people. The public preference is influenced by several factors, they are travel cost, comfort, security, and travel time. The community will still use Trans Semarang Corridor I or switch from private vehicle to Trans Semarang Corridor I if there are several factors that must be improved from Trans Semarang Corridor I. Based on the result of factor analysis, the factors that need to be prioritized or upgraded in Trans Semarang Corridor I are comfort, staff friendliness, security, rates, and facilities.